The packaging designer's book of patterns - Wybenga, George L.; Roth, Lászlo (Wiley, 2013)
"Packaging design is increasingly integral to product development activities and is among the earliest considerations of product designers and brand managers. Packaging design involves the design of the physical shape of the package, the graphic design on that package, and the integration of the packaging process into the production process"-- Provided by publisher
Keywords: Packaging -- Design; Paperboard